What Are Some Best Practices for Starting a Pump in a Distribution System?. Issue 7 (1st July 2016) - Gimson, Mark; Duque, Alejandro
Abstract : Whenever a pump is started in a distribution system, the sudden increase in flow and pressure can create pressure waves that can cause noise and damage. To avoid this, engineers find ways to slowly ramp up pump speed.